Infrared Beacons based Localization of Mobile Robot - Krejsa, J.; Vechet, S. (Elektronika ir Elektrotechnika, 2012)
The paper introduces the method for indoor localization of a mobile robot based on infrared beacons positioned stationary in the environment. The beacons provide bearing only information, fused together with either motion controllers commands or robot odometry via Extended Kalman filter to estimate the location of the robot. Simulation results include comparison with UKF and PF based localization and comparison with distance, distance/bearing beacons measurement. The verification on the test real robot with differential chassis and commercial robot with Ackerman chassis is provided. The main advantage of the method is the low cost of whole localization system. Ill. 8, bibl. 17, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1046